Clinical performance and patient-related outcome measures of digitally fabricated complete dentures: A systematic review and meta-analysis - Avelino, Maria Eduarda Lemos; Costa, Rayanna Thayse Florêncio; Vila-Nova, Taciana Emília Leite; Vasconcelos, Belmiro Cavalcanti do Egito; Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia Dantas (Elsevier, 2024)
Statement of problem: The demand to streamline workflow while increasing patient comfort and satisfaction in the manufacturing of removable complete dentures (CDs) is growing, and computer-aided design and computer-aided manufacturing (CAD-CAM) technology has gained prominence. However, a systematic review and meta-analysis of the clinical performance and patient-related outcome measures (PROMs) of digitally fabricated complete dentures is lacking. Purpose: The purpose of this systematic review and meta-analysis was to determine whether digitally fabricated CDs improve the clinical performance and PROMs compared with conventionally fabricated CDs. Material and methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and was registered at the International Prospective Register of Systematic Reviews (CRD42023433909). This review aimed to address the question “Do digitally fabricated CDs improve clinical performance and PROMs compared with conventional CDs?” Two independent authors conducted electronic searches up to September 2023. Denture base retention and patient satisfaction were analyzed through the continuous outcome evaluated by mean difference and standard deviation, with 95% confidence intervals. The risk of bias in each study was assessed using the Risk of Bias In Non-randomized Studies of Interventions and the Risk of Bias based on the Cochrane risk of bias tool for randomized trials. The certainty of evidence was assessed using Grading of Recommendations, Assessment, Development and Evaluation. Results: A total of 1505 articles were found during the search, and 16 were included in this review. The main outcomes were grouped into clinical performance (retention, adaptation or fit, clinician's denture quality assessment, masticatory efficiency, and occlusal force) and PROMs (patient satisfaction, oral health related quality of life, final choice, and willingness-to-pay). In terms of denture base retention, between conventional CDs and printed CDs analyses, conventional CDs exhibited better retention (P=.02), but no significant difference was found between the conventional CDs and milled CDs (P=.20). In terms of patient satisfaction, no statistically significant difference was found between the manufacturing methods of digitally fabricated CDs (printed CD, P=.55; milled CD, P=.08). Conclusions: Digitally fabricated CDs showed similar or better clinical performance than conventional CDs, and different types of digital manufacturing processes for complete dentures did not influence PROMs.